Exploring The Role of Tax Sanctions, Tax Awareness and Tax Knowledge in Shaping Taxpayer’s Compliance - Khatimah, Shinta Aprilia Chusnul; Muhammad Wisnu Girindratama (Journal of Economics, Business, and Government Challenges, 2024)
This study aims to investigate the influence of tax sanctions, tax awareness, and tax knowledge on tax compliance in the Surabaya area. Employing a quantitative research approach, data was collected through questionnaires from a sample of 134 taxpayers in Surabaya, selected using the purposive sampling method. The data was analyzed using Structural Equation Modelling (SEM). The findings reveal that tax sanctions and tax awareness do not significantly impact taxpayer compliance. This indicates that the implementation of tax sanctions and the current level of taxpayer awareness alone are insufficient to drive compliance with tax obligations. Conversely, tax knowledge was found to have a significant influence on taxpayer compliance, suggesting that the more knowledgeable taxpayers are about tax regulations and obligations, the more likely they are to comply. These results highlight the need for policymakers to focus on improving tax education and outreach programs, as enhancing taxpayers' understanding of tax regulations could be a more effective strategy to increase compliance than merely enforcing sanctions or raising awareness.